The intracellular cation channel TMEM176B as a dual immunoregulator - Hill, Marcelo; Russo, Sofía; Olivera, Daniela; Malcuori, Mateo; Galliussi, Germán; Segovia, Mercedes (Frontiers in Cell and Developmental Biology, 2022)
Characterizing immune regulatory pathways is critical to understand physiological and pathophysiological processes as well as to identify novel immunotherapeutic targets. The cation channel TMEM176B has emerged in the last years as a potential new immunoregulatory player and pharmacological target. Here, we review how expression data, clinical associations of genetic variants and functional studies support a dual role for TMEM176B in regulating immune responses. Thus, TMEM176B can inhibit effector immune responses in some setting whereas it may also promote immunity by supporting antigen presentation. We also discuss a potential role for TMEM176B in regulating type 2 and 3 immunity and comment recent data on modulation of DC biology and inflammasome activation as well as CD8+ T cell responses. Understanding the role of TMEM176B in immunity is critical to propose rational pharmacological approaches targeting this channel.